Ascomycetes from the tropical cloud forest of Honey, Puebla de los Angeles, Mexico - Sánchez Flores, Marcos; Valenzuela, Ricardo; Hernández-Muñoz, Marco A.; García Jiménez, Jesús; Martínez-Pineda, Michelle; Raymundo, Tania (Instituto de Ecología, A.C., 2020)
Background and Aims: Ascomycetes are a group of fungi that are characterized by the formation of ascospores within ascas, they occur in all terrestrial and marine ecosystems. The studies of this group in the cloud forest in Mexico have been increasing and a mycofloristic inventory of the municipality of Honey in the Sierra Norte in Puebla, which preserves 50% of its original vegetation, is presented here.Methods: The specimens were collected in six locations in the municipality of Honey, during the years 2016 to 2018. The specimens were studied and determined according to traditional techniques in mycology and were deposited in the fungus collections of the herbaria ENCB and FEZA.Key results: Fifty-two species of ascomycetes were determined for the municipality of Honey, of which 39 are new records for the state, while Adelphella babingtonii, Cudoniella acicularis, Lachnum fuscescens, Ophioceras leptosporum, Orbilia curvatispora and Unguiculariopsis acerina are new records for Mexico. Additionally, Hymenoscyphus herrerae is described as a new species for science. Hence, with this study there are a total of 93 species for the entity and 141 for the cloud forest from Mexico. The family Xylariaceae presented the highest taxonomic richness with 16 species, Xylaria with 14 being the best represented genus (27%) of ascomycetes from the cloud forest of Honey.Conclusions: The Ascomycetes are the best studied group of fungi in the cloud forest from Puebla; however, it is necessary to increase efforts to inventory and describe the richness of fungi and other organisms in this endangered ecosystem.